Práxis dos docentes dos cursos técnicos e tecnológicos e as demandas do mundo de trabalho : um olhar na relação teoria e prática : um foco no TheoPrax - Santos, Maria de Fátima Luz (2008)
This dissertation brings to focus of analysis the pedagogical praxis of teachers of technical and technological courses in front of influences of technologicals innovations with base in the microelectronic and on the demands of the work s world. We tried with this theme to superate the dichotomy between the theory and the practice in a investigation movement in the educative and productive institution making the analysis to light of these demands. There was a tentative of breaking the preconception about the influence of economy in education. However the author tries to not absent the analysis and critical reflexions taking out the contributions of these technologicals phenomenons for education caring to not transcribing them, and yes, interpreting them. The author methodological option allowed analyzing the technologies influences in the works' world and its requisitions on the professionals' profiles and on the decurrently jobs. Allow analyze the praxis of teachers these courses and the triad relation between epistemology, axiology and methodology through the case's study in SENAI-BA Institution. The author also does a brief analysis in the tendencies and in the technological changings in the work's world in an Industrial and developed country Germany, trying to compare the requirements and the adopted solutions by the elected country. In this way this study contributed to strength a vision of integrated systems between theory and practice. In this perspective the author considered that the approached phenomenons are connected in a relation of interdependence between areas of knowledge and professional suscitating therefore a teaching praxis in the direction of knowledge production with autonomy and creativity on the cognoscente and ethical subject formation.